Functions of the valid short participles of the present in Old Russian-Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to the analysis of old and to formation of new functions of the valid short participles of the present in Old Russian-Ukrainian language of the ХІ th – ХІІІ th centuries.
Keywords: valid short participles; definition; nominal part of a compound predicate; the coordinated and uncoordinated participle